The reliability of shear elastic modulus measurement of the ankle plantar flexion muscles is higher at dorsiflexed position of the ankle - Junya Saeki; Tome Ikezoe; Masatoshi Nakamura; Satoru Nishishita; Noriaki Ichihashi (Journal of Foot and Ankle Research, 2017)
Abstract Background Excessive stiffness of lower limb muscles is associated with sports injuries. Therefore, the identification of a reliable measurement of the shear elastic modulus of various ankle plantar flexion muscles is required to evaluate lower leg sports injuries. This study investigated the reliable measurement of the shear elastic modulus of the ankle plantar flexion muscles at different ankle positions. Methods Twenty-three healthy young men (25.3 ± 3.6 years, 172.9 ± 5.0 cm, 67.2 ± 7.2 kg) participated in this study. The shear elastic moduli of the ankle plantar flexion muscles including the lateral gastrocnemius, medial gastrocnemius, soleus, peroneus longus, peroneus brevis, flexor hallucis longus, flexor digitorum longus and tibialis posterior were measured using ultrasonic shear wave elastography at 0, 10 and 20° dorsiflexion. Results The reliability of the shear elastic modulus measurements for each ankle position was assessed. The results showed that the interday reliability of the measurements differed between ankle positions and that the reliability of the shear elastic modulus measurements at 20° dorsiflexion was higher than that at 10° or 0°. Conclusion Our results suggest that measurements at 20° dorsiflexion may provide a more reliable measurement of the shear elastic modulus of ankle plantar flexion muscles.